Corporate Legal Liability as a Criminal Act of Corruption - Lois Lodewikh Sintung; Syamsul Haling; Kaharuddin Syah (Indonesian Research Journal in Legal Studies, 2022)
The aims of this study are: (1) To find out and analyze the qualifications of corporations as subjects of corruption. (2) To find out and analyze the form of criminal liability against corporations as perpetrators of corruption. The research method used in writing the results of this thesis research is normative juridical. The results of the study show (1) the existence of corporations as the subject of criminal acts should be a benchmark in handling these cases, where law enforcement officers are often found never handling cases related to corporations before. Their understanding of the corporation is still very low. All this time, they have only dealt with conventional crimes. For this reason, it is necessary to conduct intensive socialization on matters relating to corporations to all law enforcement officers. (2) The application of criminal liability for corporations as criminal acts of corruption seems discriminatory and partial due to the uncertainty of the qualifications of the actors (plegen), as regulated in the provisions of the legislation and sometime still using the term of person/legal entity and other uncertain terms, so that the enforcement encounters some ambiguity in determining the qualifications of actors (plegen, doen plegen, medeplegen). (3) The application of the concept of criminal liability to corporations is also ambiguous and seems discriminatory and partial due to the uncertainty of the subject of the perpetrators of corporate acts which are also related to the disparity in the application of the criminal system. The researcher's suggestions are: (1) the statutory provisions that using the terminology of persons/legal entities are separated into persons or legal entities or mention directors or each person. 2) In relation to the issue of criminal liability, it is better if the provisions of the legislation stipulate the concept of criminal liability based on the qualifications of acts caused by the corporation.